The prospect of creating new pills for oral mucosa diseases - Chonka, H. (Запорізький державний медичний університет, 2019)
According to WHO official statistics, about 98% of people in the world suffer from inflammatory diseases of oral mucosa. So goal of our research became problems coverage of oral mucosa diseases in Ukraine. As materials and methods witch, we used secondary free information about pills for these pills. Our results and effects. Analyzes of market research has shown that range of pills for oral mucosa diseases have limited choice and have a selective therapeutic effect. Despite advances in the science of creating new medicines in nowadays, do not satisfy the demand for treatment of these diseases. So it’s very important created new treatment pills which based on derivatives of 1,2,4- triazolum and expasession of the domestic pharmaceutical market in Ukraine and thereby improving treatment.
Keywords: тези доповідей